Effects of Two Commercial Game Bird Feeds on Captive Northern Bobwhite Chick Growth Rates - Andrew N. Tri; Fidel Hernandez; David G. Hewitt; William P. Kuvlesky Jr. (National Quail Symposium Proceedings, 2017)
Supplemental feeding of northern bobwhites (Colinus virginianus) is a widespread management practice. Bobwhite chicks in the wild consume only arthropods for their first 30–60 days of life. Arthropods may become less abundant and managers have supplied bobwhites with supplemental feed during times of drought to mitigate the lack of arthropods. We compared growth rates of captive bobwhite chicks consuming a new, commercial 24% crude protein supplement to growth rates of bobwhites consuming a commercial 30% crude protein complete ration. There was no male/female bias related to chick growth. Chicks consuming the 24% protein diet grew slower and reached adult mass (150 g) 1 month later than birds on the 30% protein diet. Birds grew 4–6 times faster than documented rates from wild chicks in Florida, but this is attributed to captivity bias. A 24% protein supplement has insufficient protein to optimize growth of bobwhites and is a poor substitute for arthropods in time of drought. A 30% protein diet has sufficient nutrient levels to justify further research as a supplement to mitigate a lack of arthropods in times of drought.
Keywords: chicks; Colinus virginianus; growth; northern bobwhite; protein pellets; supplemental feed